The outcome of Chronic lymphocytic leukaemia patients with 97% IGHV gene identity to germline is distinct from cases with <97% identity and similar to those with 98% identity. (5th February 2016) - Davis, Zadie; Forconi, Francesco; Parker, Anton; Gardiner, Anne; Thomas, Peter; Catovsky, Daniel; Rose‐Zerilli, Matthew; Strefford, Jonathan C; Oscier, David
Summary: IGHV gene mutational status has prognostic significance in chronic lymphocytic leukaemia (CLL) but the percentage of mutations that correlates best with clinical outcome remains controversial. We initially studied 558 patients from diagnosis and found significant differences in median time to first treatment (TTFT) among Stage A patients and in overall survival (OS) for the whole cohort, between cases with <97% and 97–98·99% identity and between cases with 97–98·99% and ≥99% identity, when cases from the IGHV3‐21 Stereotype Subset #2 were excluded. A significant difference in progression‐free survival (PFS) and OS between those with <97% and 97–98·99% identity, but not between those with 97–98·99% and ≥99% identity was also observed in a validation cohort comprising 460 patients in the UK CLL4 trial. Cox Regression analyses in the Stage A cohort revealed that a model which incorporated <97%, 97–98·99% and ≥99% identity as subgroups, was a better predictor of TTFT in CLL than using the 98% cut‐off. Multivariate analysis selected the three mutational subgroups as independent predictors of TTFT in Stage A patients, and of OS in the diagnostic cohort. This study highlights that cases with 97% identity should not be considered to have the same prognosis as other cases with mutated IGHV genes defined as <98% identity to germline.